Local production of tenascin-C acts as a trigger for monocyte/macrophage recruitment that provokes cardiac dysfunction. (10th November 2017) - Abbadi, Dounia; Laroumanie, Fanny; Bizou, Mathilde; Pozzo, Joffrey; Daviaud, Danièle; Delage, Christine; Calise, Denis; Gaits-Iacovoni, Fréderique; Dutaur, Marianne; Tortosa, Florence; Renaud-Gabardos, Edith; Douin-Echinard, Victorine; et al.
Abstract: Aims: Tenascin-C (TNC) is an endogenous danger signal molecule strongly associated with inflammatory diseases and with poor outcome in patients with cardiomyopathies. Its function within pathological cardiac tissue during pressure overload remains poorly understood. Methods and results: We showed that TNC accumulates after 1 week of transverse aortic constriction (TAC) in the heart of 12-week-old male mice. By cross bone marrow transplantation experiments, we determined that TNC deposition relied on cardiac cells and not on haematopoietic cells. The expression of TNC induced by TAC, or by administration of a recombinant lentivector coding for TNC, triggered a pro-inflammatory cardiac microenvironment, monocyte/macrophage (MO/MΦ) accumulation, and systolic dysfunction. TNC modified macrophage polarization towards the pro-inflammatory phenotype and stimulated RhoA/Rho-associated protein kinase (ROCK) pathways to promote mesenchymal to amoeboid transition that enhanced macrophage migration into fibrillar collagen matrices. The amplification of inflammation and MO/MΦ recruitment by TNC was abrogated by genetic invalidation of TNC in knockout mice. These mice showed less ventricular remodelling and an improved cardiac function after TAC as compared with wild-type mice. Conclusions: By promoting a pro-inflammatory microenvironment and macrophage migration, TNC appears to be a key factor to enable the MO/MΦ accumulation within fibrotic hearts leading to cardiac dysfunction. As TNC is highly expressed during inflammation and sparsely during the steady state, its inhibition could be a promising therapeutic strategy to control inflammation and immune cell infiltration in heart disease.